La fin du maton ? Transformation de la relation carcérale et rationalisation du maintien de l’ordre dans les modules de respect - Valérie Icard (Criminocorpus, 2019)
This article deals with the issue of prison protests, with regard to the evolutions of order maintaining in contemporary French prisons. We analyse the new instruments institution is providing itself with in order to counteract and contain prisoners’ protests. In this perspective, we propose a reflection on Respect modules, a new prison regime imported from the Spanish penitentiary model. It's a pluridimensional dispositive of order maintaining, which rests on an ambivalent disciplinary and governmental style. A sociological study carried out in a French prison proved that this regime allows to efficiently take control of detention. While promoting a dynamic security approach, the Respect module grants the prison officers with a new discretionary power of sanction which consolidate their authority. With the analysis of staff-prisoner relationships, the aim is to describe the sophistication of power in prison and the renewal of ways to subdue prisoners.